The development of the grammatical competence through direct corrective feedback among ninth-year students at unidad educativa Emiliano Ortega Espinoza of the city of Catamayo during the 2016-2017 school year - Ruiz Armijos, Jenny Susana (2018)
The general objective of this investigation was to develop the grammatical competence through direct corrective feedback strategy, during the study the following methods were used; Scientific, Descriptive, Analytic-Synthetic and Statistical, which allowed analyze the gathered information. The instruments used to collect the data were: test, questionnaires and observation sheets, which were applied before, during and after the intervention plan. It was designed for 8 weeks and applied to 11 students at ninth-year of basic education. The main results after applying direct corrective feedback were that the students improved in the grammatical competence aspects such as: declarative sentences, yes/no questions, informative questions, subject verbal agreement and parts of speech. As conclusion, the application of the direct corrective feedback strategy was effective in helping students to recognize their grammatical errors and improve their grammatical competence.